Detection of a tentative alphanucleorhabdovirus infecting Carica papaya in Costa Rica - Garita Salazar, Laura Cristina (2026)
Background/Objective. Foliar chlorosis, short internodes, and curved petioles with purple streaks were observed in papaya (Carica papaya) crops (North and Atlantic regions) in Costa Rica since 2014. Identification of a putative plant virus associated with these symptoms was the aim of this research. Experimental development. Plant material was tested by ELISA (four plant viruses and potyviruses group), transmission electron microscopy (TEM), RT-PCR (degenerate primers for plant viruses), sequencing and phylogenetics. Results. All ELISA tests resulted negative. Bullet-shaped particles inside nuclei, and reticulum endoplasmic were only observed by TEM in symptomatic plants. Amplicons of 900 bp were consistently obtained from symptomatic samples using degenerate primers for plant rhabdoviruses. Nucleotide sequences showed 95.6 and 96.8% similarity to a putative papaya alphanucleorhabdovirus (Alphanucleorhabdovirus, Rhabdoviridae). Conclusion. This is the first report of a putative alphanucleorhabdovirus associated with symptomatic papaya plants showing streaked petiole (“pecíolo rayado”) disease in Costa Rica, but Koch’s postulates must be fulfilled and vector identified.